2018
DOI: 10.3390/molecules23020443
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the E–E’ Bonds (E, E’ = S and Se) in Glutathione Disulfide and Derivatives Elucidated by Quantum Chemical Calculations with the Quantum Theory of Atoms-in-Molecules Approach

Abstract: The nature of the E–E’ bonds (E, E’ = S and Se) in glutathione disulfide (1) and derivatives 2–3, respectively, was elucidated by applying quantum theory of atoms-in-molecules (QTAIM) dual functional analysis (QTAIM-DFA), to clarify the basic contribution of E–E’ in the biological redox process, such as the glutathione peroxidase process. Five most stable conformers a–e were obtained, after applying the Monte-Carlo method then structural optimizations. In QTAIM-DFA, total electron energy densities Hb(rc) are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…A E---B E of A E 2 B E 2 σ(4c-6e) has been elucidated [24][25][26][27] using the quantum theory of atoms in molecules (QTAIM) approach, introduced by Bader [28][29][30][31][32][33][34][35][36][37]. e linear interactions of the σ(4c-6e) type will form if B E in A E 2 B E 2 is replaced by X, giving E 2 X 2 σ(4c-6e).…”
Section: E Nature Of B E---a E and A E-a E In B E---a E-mentioning
confidence: 99%
“…A E---B E of A E 2 B E 2 σ(4c-6e) has been elucidated [24][25][26][27] using the quantum theory of atoms in molecules (QTAIM) approach, introduced by Bader [28][29][30][31][32][33][34][35][36][37]. e linear interactions of the σ(4c-6e) type will form if B E in A E 2 B E 2 is replaced by X, giving E 2 X 2 σ(4c-6e).…”
Section: E Nature Of B E---a E and A E-a E In B E---a E-mentioning
confidence: 99%
“…GSSG is radical so it must be reduced to GSH immediately. 9,10,11 Recently, study about selenium in elderly still rarely. Baierle et al 12 in 2015 found negative correlation between GPx activity with plasma carbonyl in elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the B E··· A E and A E– A E in B E··· A E– A E··· B E at naphthalene peri‐positions was elucidated by employing the quantum theory of atoms‐in‐molecules (QTAIM) approach . The nature of the X···E and E–E in X···E–E···X was similarly clarified.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] The nature of the B E··· A E and A E-A E in B E··· A E-A E··· B E at naphthalene peri-positions was elucidated by employing the quantum theory of atoms-in-molecules (QTAIM) approach. [17][18][19][20] The nature of the X···E and E-E in X···E-E···X was similarly clarified. X 4 σ(4c-6e) of the n p (X-)→σ*(X-X)←np(X) type is also expected to stabilize the linear alignment of four halogen atoms (X) of the σ-type.…”
mentioning
confidence: 98%